THE APPLICATION OF BEHAVIOURAL FINANCE TO ENHANCE VOLUNTARY RETIREMENT SAVINGS – ARE THE SOLUTIONS UNIVERSAL AROUND THE WORLD? - Sieczkowski, WOJCIECH (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
Behavioural finance is a promising solution to enhance voluntary retirement savings (VRS) and is gaining recognition around the world. Despite this, there may be some limitations to the transferability of its applications. This paper summarizes the key findings relevant to long-term savings and then analyses these aforementioned limitations, by first pointing to some methodological assumptions made, and then looking at the potential set of variables impacting the applications’ transferability.